Analysis of the seismic effects of the local slope site of Longtoushan market town in Ludian Ms6.5 earthquake - Du, Liting; Jin, Liguo; Zhou, Zhenghua (Frontiers in Earth Science, 2023)
In the Ludian Ms6.5 earthquake (Yunnan, China), Longtoushan market town and its vicinity showed significant differences in earthquake damage. To explain this phenomenon, this paper discusses the local engineering geological conditions, local topographic effects, and seismic response of the soil layer in Longtoushan market town. The results show that complex topography and varied engineering geological conditions will lead to significant differences in ground motion, and then lead to significant differences in building earthquake damage. Slope topography has an obvious influence on ground motion. From the foot of the slope to the top of the slope, the degree of influence gradually increases, and the influence in different directions is different, as shown: the closer to the top of the slope, the more significant the difference. This indicates that the serious damage to buildings built on the slope is caused by the amplification effect of local terrain and the differential effect of ground motion. Although the site belongs to Class II site, the near-surface geotechnical properties and their combination characteristics, the physical state and thickness of the overlying soil layer, the variation characteristics of shear wave velocity, the nonlinear dynamic characteristics of the soil, and other factors play a decisive role in the amplification degree of ground motion. The significant difference in ground motion on the surface of the slope site leads to a significant difference in seismic damage to buildings on the site. The covering soil layer has a significant effect on the acceleration response spectrum. The conclusions obtained in this paper can provide a scientific basis for the site selection of engineering construction and seismic design of building structures.